EXPERIMENTAL STUDY ON THE EFFECT OF PV TILT ANGLE ON MINI SOLAR POWER BANK PERFORMANCE - Putra Andi Kolala; Lathifa Putri Afisna; Wuwuh Saminto Wibowo; Aditya Septian Putra; Antonio Carlo; Fajar Bagas Pambayun; Fajar Nur Huda (Department of Mechanical Engineering Education, 2026)
Solar panels are devices designed to convert solar energy into electrical energy through the photovoltaic (PV) effect, offering a sustainable solution for portable power needs. This study investigates the effect of solar panel tilt angles on the performance of a mini solar cell power bank in Institut Teknologi Sumatera, South Lampung, Indonesia. A 2.5 W monocrystalline silicon panel was tested at tilt angles of 15°, 30°, and 45°. Data on current, voltage, temperature, and power were collected at 30-minute intervals from 09:00 to 15:00 WIB over three separate clear-sky measurement days. The results indicate that the 15° tilt angle produced the highest average current (38.39 mA), voltage (4.08 V), and power (0.162 W). The estimated charging time for a 3000 mAh battery was 93.77 hours (15°), 116.13 hours (30°), and 138.04 hours (45°). The 15° tilt is the optimal configuration for portable solar power banks in this tropical region.